Pemaknaan Filsafati Kearifan Lokal untuk Adaptasi Masyarakat terhadap Ancaman Bencana Marin dan Fluvial di Lingkungan Kepesisiran - S Sunarto (Forum Geografi, 2011)
The purpose of this research was to study the philosophical meaning of local wisdom that developed in the communities in the coastal environment, particularly in the eastern coast of Central Java. The method used for this philosophical meaning using the approach of geomorphological hermeneutics and disaster semiotics. The results of this research indicate that identified local wisdom in the form of cultural semiotics and faunal semiotics to anticipate the hazards of climate change as marine hazard and fluvial hazard. Cultural semiotics found in the form of advice that still need to be interpreted with a geomorphological hermeneutics approach order to use it to adapt to the coastal environment against marine hazard. The cultural semiotics has a geomorphological philosophical meaning as natural cycle that leads to dynamic equilibrium, not the philosophical meaning that leads to the view of anthropocentrism. In addition, also found cultural semiotics of “Dina Rèntèng” based on the philosophical views of ecocentrism. The cultural semiotics is used in society to adapt to the fluvial hazard. Faunal semiotics found in the form of anomalous crab behavior as a form of adaptation due to its response to environmental condition. The faunal semiotics has been used as a guide for the community to adapt to the fluvial hazard. Because of the local wisdom is loaded with philosophical meaning, it can be metatourism assets, so it can convert harm into benefit.